2005
DOI: 10.1055/s-2004-832406
|View full text |Cite
|
Sign up to set email alerts
|

Zementierte Hüftendoprothetik in Deutschland - ein Update

Abstract: The results of this survey demonstrated that, in comparison to 1998, the current state of cemented THA, in particular cementing technique has significantly improved. Future emphasis should be on continued surgeon education and training, as the operative, i. e., cementing techniques are of utmost importance for long-term success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
1
0
5
Order By: Relevance
“…Varying properties of bone cements can lead to different levels of penetration into the tibia apophysis. In vitro studies demonstrated a significant influence of penetration on the initial component stability in TKA [11,22,23]. Limited experimental and clinical data exist for the material properties of the Refobacin ® Bone Cement R. Kock et al [6] compared the chemical composition, handling properties, and ISO standard mechanical testing of four different bone cements in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Varying properties of bone cements can lead to different levels of penetration into the tibia apophysis. In vitro studies demonstrated a significant influence of penetration on the initial component stability in TKA [11,22,23]. Limited experimental and clinical data exist for the material properties of the Refobacin ® Bone Cement R. Kock et al [6] compared the chemical composition, handling properties, and ISO standard mechanical testing of four different bone cements in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Durch die immer weiter fortschreitende Entwicklung in der Hüftgelenken-doprothetik nimmt diese Behandlungsform bei jährlich etwa 500.000 implantierten Hüftendoprothesen in Europa eine zentrale Rolle in der unfallchirurgischen und orthopädischen Tätigkeit ein [68,77]. In Deutschland werden jährlich etwa 200.000 Hüftendoprothesenoperationen mit einer Vielzahl von Prothesenmodellen durchgeführt [55], von denen etwa 10% zementiert werden [50]. Die Zahl der Wechseloperationen in Deutschland liegt derzeit zwischen 5 und 10% [55].…”
Section: Wann Wird Zementiert? Hüftendoprothetikunclassified
“…Die Erkenntnisse führten über die Jahre hinweg zu einer sukzessiven Verbesserung der Techniken mit Erweiterungen in verschiedenen Generationen der Zementiertechnik (l " Abb. 1)[28]. Diese Weiterentwicklungen spiegeln sich auch in neueren Untersuchungen des Schwedenregisters wider[4].…”
unclassified